(3QaY GdMLH GdeSJhQI Yf eMGSf GdebUhQIs - (3CHh GdbGSe eMeO Hf CMeO Hf eMeO GdMSjfj GdSHJi GdeYQha HGdTQja CHh GdZQfGWis; (3MGRe GdbQWGLfj , MGRe Hf eMeO Hf MSf Hf MGRe, CHh GdMSf,J (B684 (3g` s
(3ChdgG (B:s
(3hHYO aEfi deG JCedJ ebUhQI GdGeGe GdChMO CHj GdMSf CdajJgG JLeY VQhHG ef GdGMSGS hJTJed Ydi CaGfjf ef GdHjGf s
(3BNQgG (B:s
(3hGJjJ HeG jMUd efg GdbGQF Ydi QTGO abO hajJ HeG hYOJ s
(3fSNI KGdKI JJab ai ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa ai HYV GdCdaGX s
(3hYdjg JMHjS Ydi LGeY GdbQhjjf HaGS HJGQjN (B156 (3g`s
(3hYdjgG JUMjMGJs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs